Uso de compostos extraídos da manga (Mangifera indicus) no controle da oxidação lipídica na carne de frango, em produto cárneo tipo mortadela e ovos de consumo - Borges, Ângela da Silva (2009)
The present study aimed to evaluate the effects of addition of natural antioxidants from mango in the feed of the broiler chickens and laying hens on the oxidative stability of chicken meat, a product processed from this meat (chicken mortadella) and eggs for consumption. It was prepared two ethanolic extracts from the peel (E1) and (E2) mango seed. The dried extracts were used in two bioassays, one with chickens and one with laying hens. In both trials, the alimentary treatments consisted in control, T1, feed without addition of extracts, T2, feed with addition of 200 ppm of butylated hydroxytoluene (BHT), T3 and T4, feed with 200 and 400ppm of extract of the mango peel, respectively, and T5 and T6, feed with 200 and 400ppm extract of the mango seed, respectively. In the trial with chickens, 360 chicks in a day, from Ross line were used, which were distributed randomly among the six treatments with six replicates of 10 poultry. In the trial with laying hens, 180 poultry from Hisex x Whitwam line, with 40 weeks of age were used, which were randomly distributed among six treatments with five replicates of six poultry. The meat of the broiler chickens was used for the Experiments 1 and 2 and the eggs of the laying hens for the Experiment 3. In Experiment 1, four poultry with 42 days of age, were selected and after slaughter, the boneless breasts were collected, split in half and vacuum packed. The samples of left breasts were stored under refrigeration (4 oC) and the rights breasts under freezing (~20 oC). The analyses of color and lipid oxidation of the meat were performed at 0, 5, 10 and 15 days in the refrigerated samples, and at 0, 30, 60 and 90 days in the frozen samples. In Experiment 2, the same chickens from Experiment 1 were used, whose the sections of the leg and thigh were collected and after boning and skinning the meat was used in the formulation of mortadella which were stored under refrigeration (4 oC) for 90 days. During the storage of meat product were carried out color (CIE Lab system) and lipid stability (TBARS) analysis at 0, 30, 60 and 90 days. In Experiment 3, it was selected 25 eggs from each replicate which were stored under refrigeration (4 oC) and analysis of color (color fan and the CIE Lab) and lipid oxidation (TBARS) of yolk were realized at 0, 15 , 30, 45 and 60 days. In Experiment 1, it was observed a reduction of L * values (brightness) in chicken breast during storage under freezing, and an increase in a* value (redness) during storage under refrigeration. The values of TBARS suffered considerable increase in all treatments during storage under refrigeration or freezing. Compared with the control treatment (T1), treatments containing BHT (T2) or extracts E1 and E2 at concentrations of 200 and 400 ppm (T3, T4, T5 and T6) were effective in controlling lipid oxidation of breast meat chicken chilled for 5 days or frozen for 3 months. In Experiment 2, the storage of the mortadella for 90 days resulted in reduction of the L* value and increases of the a* and b* values. The chicken meat products in all treatments had elevated values of TBARS with increase in storage time. During storage under refrigeration, T2 and T6 treatments were the most effective in controlling lipid oxidation in mortadella. In experiment 3, there was no significant variation in the color component L * of the eggs yolk from the T2, T3, T4, T5 and T6 treatments compared to the control treatment (T1), throughout the storage period. The a* values was increased with the storage time for all treatments, while for the b* values there was no significant difference between treatments. In relation to the color measured by yolk color fan, the treatments had no significant effect in comparison to control treatment (T1), throughout the storage period. The lipid oxidation of egg yolk from added-antioxidant treatments (T2, T3, T4, T5 and T6) was smaller than the eggs from the control treatment (T1), but increased during storage of eggs. The eggs from T5 treatment had the lowest rate of increase in lipid oxidation at the end of the storage period, followed by those of T4 and T6 treatments, respectively. It was concluded that the extracts of peels and seed of mango can be used in poultry feed to help control lipid oxidation poultry products and eggs.